Clinico-epidemiological profile and diagnostic procedures in suspected pediatric tuberculosis in a tertiary care centre in Tamil Nadu - Ramanathan, Ramanathan; Mohankumar, Jayapritha (International Journal of Contemporary Pediatrics, 2025)
Background: Childhood tuberculosis (TB) remains a significant public health challenge, particularly in developing countries like India. Pulmonary TB is predominant in children, but a substantial proportion also present with extrapulmonary TB. This study aims to analyze clinico-epidemiological profile and diagnostic procedures in suspected pediatric TB cases at a tertiary care center in Cuddalore. Methods: A hospital-based cross-sectional study was conducted from January 2023 to June 2024, involving 200 children suspected of having TB who presented to the pediatrics department. Data were collected using a pretested proforma, capturing socio-demographics, clinical features, and diagnostic procedures. Diagnostic confirmation was made using various diagnostic methods. Statistical analysis performed using SPSS version 25, with chi-square tests to assess associations. Results: The study included 200 suspected children with a mean age of 7.47 years. Extrapulmonary TB was more prevalent (67.5%) than pulmonary TB (32.5%). Majority (85%) were from rural areas, with significant associations between extrapulmonary TB and malnutrition, lymph node involvement, and specific diagnostic modalities. 11.25% of cases were microbiologically confirmed through CBNAAT. Extrapulmonary TB was diagnosed primarily via cytopathology and imaging, whereas pulmonary TB cases were often identified by chest X-ray and CBNAAT. Conclusions: The findings highlight high prevalence of extrapulmonary TB among children in rural, economically disadvantaged areas, with malnutrition being a significant risk factor. It underscores the need for enhanced diagnostic capabilities, especially in resource-limited settings, to improve TB detection. Expanding access to molecular diagnostics and integrating nutritional interventions are essential for better management.